HOST RESPONSES OF WHEAT GENOTYPES TO PRATYLENCHUS BRACHYURUS AND MELOIDOGYNE JAVANICA - Gonçalves, Diego Francisco; Lopes, Ana Paula Mendes; Puerari, Heriksen Higashi; Dias-Arieira, Claúdia Regina (Scientia Agraria, 2018)
This work aimed to evaluate the host response of twelve wheat genotypes to Pratylenchus brachyurus and Meloidogyne javanica in two distinct periods. Tests were carried out in greenhouse with an initial population of 1,200 nematodes per pot, each containing 700 mL substrate and seven wheat seedlings. Evaluation was done at 60 and 83 days after inoculation in the first and the second experiment, respectively. At 60 days after inoculation with P. brachyurus, all cultivars were resistant to the nematode, presenting reproduction factor RF <1. At 83 days after inoculation, only the cultivars F. Cristalina and IPR 85 showed RF <1, the others were susceptible to the P. brachyurus. At 60 days after M. javanica inoculation, BRS Sabiá, F. Cristalina, IPR 144, IPR Catuara Tm, Quartzo and FPS Nitron presented RF> 1. At 83 days, cv. Gralha Azul, in addition to those already mentioned, presented RF>1. The cultivars BRS Gaivota and IPR 85 were susceptible to M. javanica in both experiments. It was concluded that the twelve wheat genotypes presented different host responses to the studied nematodes and most of them were susceptible.